MTUN seals MoU with JPPKK empowers national TVET - Mimi Rabita, Abdul Wahit (UMPSA, 2022)
BANGI, 2 June 2022 - In an effort to promote the country’s technical education, a strategic relationship and collaboration was sealed between the Department of Polytechnic Education and Community Colleges (JPPKK) and the Malaysian Technical University Network (MTUN) involving four universities, namely Universiti Malaysia Pahang (UMP), Universiti Malaysia Perlis (UniMAP), Universiti Tun Hussein Onn (UTHM) and Universiti Teknikal Malaysia Melaka (UTeM).